KGB and territory control - Anušauskas , Arvydas (Genocidas ir rezistencija, 2006)
To control society and its relations with people living in other countries, as well as their movements (migration, emigration, tourism), the KGB had to create a system of ‘territorial control’. Its most difficult features were: (i) reducing the area under control and limiting the remaining territory by introducing a system of prohibitions; (ii) reducing the number of people under control and limiting the movement of the reminder people by introducing a system of prohibitions. This allowed the KGB to exercise selective rather than universal control over certain areas, i.e., certain pre–defined groups of people, certain pre–defined human relations, and certain pre–defined territories. Without the system of prohibitions – official and unofficial ones – approved by published laws and secret departmental normative acts (instructions, resolutions, and orders) – the KGB would not have been able to organise its operations and to carry out the tasks set by the ruling communist nomenclature.
Keywords: KGB; economic; tourism; Jews; Poland